PENGARUH PENGGUNAAN BUKU SAKU SEBAGAI MEDIA EDUKASI TERHADAP KEPATUHAN DIET DAN KADAR GULA DARAH PUASA (GDP) PADA PASIEN DIABETES MELITUS TIPE 2 DI KECAMATAN SUMBANG BANYUMAS - Burkon, Lily Kusumasita; Nafiisah, Nafiisah; Ernawati, Dwi Arini; Putri, Chilma Al Aini (Mandala Of Health, 2024)
Background: Indonesia ranks 6th highest with Diabetes mellitus (DM) in the world in 2019. There are complications occur due to DM type 2. To prevent this, fasting blood sugar (GDP) monitoring and patient diet by using pocketbooks as an educational compliance can be carried out. Objective: To identify the effect of using pocketbooks as an educational medium in monitoring dietary compliance and GDP levels of type 2 DM patients in Sumbang. Methodology: Quasi-Experimental method was used with pretest – posttest design on 100 DM Prolanis patients at Puskesmas Sumbang 1 and 2 which were divided into two groups. Both groups were given different education where the treatment group used a pocketbook while the control group was given oral education. Results: In the pretest-posttest data of GDP levels, there were differences in results before and after the intervention in the treatment group (Wilcoxon test, p = 0.000) while the control group gave no difference in results before and after the intervention (Wilcoxon test, p = 0.090). In the pretest – posttest diet adherence data, there were differences in results before and after the intervention in the treatment group (Paired T Test, p = 0.000) while the control group gave no difference in results before and after the intervention (Paired T Test, p = 0.074). The Mann Whitney test and the unpaired T test showed that the two variables had a significant difference (p = 0.000). Conclusion: there is an effect of pocketbook education intervention on GDP levels and dietary compliance of type 2 DM patients in Sumbang District, Banyumas Regency which reduces GDP levels and improves respondents' dietary compliance.